(untitled) (Applied Biological Research, 2012)
Eighteen mongrel dogs of either sex were divided into three equal groups of six animals each, and were subjected to three different renal biopsy techniques viz., ultrasound-guided biopsy using 14-G Tru-cut biopsy needle (Group A), ultrasound-guided fine-needle aspiration biopsy (Group B) and laparoscope-guided biopsy using laparoscopic biopsy forceps (Group C) to study the changes in various haemato-biochemical parameters. The estimations were made just before and at 24, 48 and 72 h post-biopsy. Haematological parameters (Hb, PCV, TLC and DLC) and serum protein remained within the normal reference range in all groups throughout the study period and did not show any significant alterations at any observation interval within and amongst the groups. In all groups, serum creatinine and urea nitrogen increased at 24 h post-biopsy, started to decrease thereafter and by the end of study period the values reached nearer to their corresponding base values. Serum sodium values showed significant (P <0.05) decrease only at 48 h post-biopsy interval in the animals of group A and it was also significantly (P < 0.05) different from corresponding value in group C. Serum sodium values showed non significant variation throughout the study period in the animals of group B and C. The group B values were significantly different from corresponding values of other groups at all post-biopsy intervals.